2004
DOI: 10.1093/humrep/deh102
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of human embryonic stem cell lines from frozen-thawed blastocysts using STO cell feeder layers

Abstract: This study indicates that establishment of hES cells from frozen-thawed blastocysts minimizes the ethical problem associated with the use of human embryos in research and that the STO cell feeder layer can be used for the culture of hES cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0
4

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(50 citation statements)
references
References 22 publications
1
45
0
4
Order By: Relevance
“…In fact, there was a first peak of generation of new hESC lines in 2004, contributed mostly from one group in the USA [12], one in Korea [13] and two in Sweden [14,15], which accounted for 16, 9 and 10 of the total of 38 new cell lines derived that year, respectively (Fig. 1).…”
Section: Gathering Information From Human Embryonic Stem Cell Registriesmentioning
confidence: 99%
“…In fact, there was a first peak of generation of new hESC lines in 2004, contributed mostly from one group in the USA [12], one in Korea [13] and two in Sweden [14,15], which accounted for 16, 9 and 10 of the total of 38 new cell lines derived that year, respectively (Fig. 1).…”
Section: Gathering Information From Human Embryonic Stem Cell Registriesmentioning
confidence: 99%
“…The mouse embryonic fibroblast cell line, STO, has been used to establish nine cell lines from frozen blastocysts and zygotes (Park et al, 2004). The advantage of STO cells over primary cultures of MEFs is that, being immortalized, they are easy to maintain and propagate.…”
Section: Alternative Feeder Cellsmentioning
confidence: 99%
“…In 2003, Park et al [20] first demonstrated that STO cells have the potential to support the establishment and maintenance of human ESC lines. Thereafter, STO cells have been widely used as feeder cells for human ESC and iPSC culture [24,25]. Proteome analyses have revealed that STO cells produce unique protein species, such as insulin-like growth factor binding protein 4 (IGFBP-4), pigment epithelium-derived factor (PEDF) and secreted protein acidic and rich in cysteine (SPARC, also known as osteonectin), which may be associated with differentiation and cell growth [26].…”
Section: Mouse-derived Feeder Cellsmentioning
confidence: 99%